Midwives' views of an evidence-based intervention to reduce caesarean section rates in Ireland. Issue 6 (November 2022) - Corrigan, Siobhán; Howard, Vivienne; Gallagher, Louise; Smith, Valerie; Hannon, Kathleen; Carroll, Margaret; Begley, Cecily
Abstract: Problem: A worldwide increase of caesarean section (CS) rates has been estimated at a rate of 4% per year and numerous interventions to reduce the rates have not been successful, perhaps because they are not acceptable to clinicians. Background: A caesarean section (CS) can be a life-saving operation, but has been associated with short- and long-term risk factors and shown to affect subsequent pregnancies. Aim: To explore midwives' views on CS rates and evaluate the feasibility and acceptability of an evidence-based intervention programme (REDUCE) designed to decrease overall CS rates in Ireland by 7%. Methods: Following ethical approval, a qualitative exploratory design was used to seek midwives' views of the evidence-based intervention. A total of 28 midwives from one large tertiary maternity hospital took part in four focus group interviews. Data were analysed using thematic analysis. Findings: Five themes emerged, illustrating the midwives' views of what could be improved in the present system and how CS rates could be reduced in future. The themes included: (i) Induction of labour; (ii) Education; (iii) Auditing of practice; (iv) Clinical practice; (v) Midwife-Obstetrician collaboration. Discussion: This study noted a rising CS rate year on year, with a rate of 37% at the time of the study, and the midwives voiced their very real concerns over the increased high rates. Conclusion: The study provided support for the evidence based 'REDUCE' intervention, which now needs to be tested empirically within this Irish population.